Coronavirus Usurps the Autophagy-Lysosome Pathway and Induces Membranes Rearrangement for Infection and Pathogenesis - Liang, Haowei; Luo, Dan; Liao, Hai; Li, Shun (Frontiers in Microbiology, 2022)
Autophagy is a crucial and conserved homeostatic mechanism for early defense against viral infections. Recent studies indicate that coronaviruses (CoVs) have evolved various strategies to evade the autophagy–lysosome pathway. In this minireview, we describe the source of double-membrane vesicles during CoV infection, which creates a microenvironment that promotes viral RNA replication and virion synthesis and protects the viral genome from detection by the host. Firstly, CoVs hijack autophagy initiation through non-structural proteins and open-reading frames, leading to the use of non-nucleated phagophores and omegasomes for autophagy-derived double-membrane vesicles. Contrastingly, membrane rearrangement by hijacking ER-associated degradation machinery to form ER-derived double-membrane vesicles independent from the typical autophagy process is another important routine for the production of double-membrane vesicles. Furthermore, we summarize the molecular mechanisms by which CoV non-structural proteins and open-reading frames are used to intercept autophagic flux and thereby evade host clearance and innate immunity. A comprehensive understanding of the above mechanisms may contribute to developing novel therapies and clinical drugs against coronavirus disease 2019 (COVID-19) in the future.